Osteoporotic bone fracture risk assessment in Latvian patients with newly diagnosed sarcoidosis - Ruza, Ieva; Lucane, Zane; Vanaga, Elina; Persana, Marta; Vitenberga-Verza, Zane; Strumfa, Ilze (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Increased calcitriol synthesis in sarcoid granulomas with subsequent hypercalcaemia and hypercalciuria can affect bone metabolism in patients with sarcoidosis. Multiple factors can increase the fracture risk in patients with sarcoidosis. This study aimed to evaluate a 10-year osteoporotic and a 10-year hip fracture risk and to analyse factors affecting fracture risk for patients with newly diagnosed sarcoidosis compared to an age- and gender-matched control group from a real-world setting. Methods: The cross-sectional study included 171 patients with a histologically verified diagnosis of sarcoidosis who were hospitalised due to suspected sarcoidosis within two years and an age- and gender-matched control group of 178 hospitalised individuals. QFracture algorithm questions were asked during interviews. Results: A cohort of 349 subjects was analysed. The median age in the patient group was 40 years (IQR:20), and 60.2% were female. 21.6% of patients with sarcoidosis had at least one comorbidity that could potentially influence the osteoporotic fracture risk. Both the median 10-year osteoporotic fracture risk (0.9% (IQR:2) vs 1.3% (IQR:2.3), p=0.005; U=12394) and a 10-year hip fracture risk (0.1% (IQR:0.3) vs 0.2% (IQR:0.5), p=0.003; U=12368.5) was lower in patients with sarcoidosis compared to control group subjects. As compared to the control group, individuals with sarcoidosis exhibited a lower frequency of both osteoporotic (2.4% vs 11.2%, OR=0.189 (95% CI:0.063-0.566), p=0.003) and low-energy trauma fractures (2.9% vs 11.8%, OR=0.225 (95% CI:0.083-0.612), p=0.003) in personal medical history. Conclusions: This was the first study to investigate osteoporotic fracture risk and related factors in Latvian patients with newly diagnosed sarcoidosis. Our data show a lower risk of a 10-year osteoporotic and a 10-year hip fracture risk in patients with sarcoidosis compared to age- and gender-matched control group subjects from a real-world setting.